2000
DOI: 10.1177/089686080002000510
|View full text |Cite
|
Sign up to set email alerts
|

What is the Optimal Frequency of Cycling in Automated Peritoneal Dialysis?

Abstract: Objective The recent increase in the use of automated peritoneal dialysis (APD) has led to concerns about the adequacy of clearances delivered by this modality. Few clinical studies looking at the effects of varying the individual components of the APD prescription on delivered clearance have been done, and most published data are derived from computer modeling. Most controversial is the optimal frequency of exchanges per APD session. Many centers prescribe 4 to 6 cycles per night but it is unclear if this is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 19 publications
(35 reference statements)
2
26
0
Order By: Relevance
“…In contrast, Hölttä et al 10 found similar total albumin losses in the dialysate in pediatric patients on CCPD and TPD. In the study by Perez et al, 21 there was also no difference in protein loss between non-tidal APD (5 Â 2, 7 Â 2 and 9 Â 2 l) and 50% TPD (treatment volume 14 l). In agreement with these results there was neither an influence of dialysate flow nor of treatment modality (50% TPD vs IPD) on total protein and albumin loss into the dialysate in our previous study.…”
Section: Protein Lossmentioning
confidence: 78%
See 3 more Smart Citations
“…In contrast, Hölttä et al 10 found similar total albumin losses in the dialysate in pediatric patients on CCPD and TPD. In the study by Perez et al, 21 there was also no difference in protein loss between non-tidal APD (5 Â 2, 7 Â 2 and 9 Â 2 l) and 50% TPD (treatment volume 14 l). In agreement with these results there was neither an influence of dialysate flow nor of treatment modality (50% TPD vs IPD) on total protein and albumin loss into the dialysate in our previous study.…”
Section: Protein Lossmentioning
confidence: 78%
“…No data on treatment volumes are included in this abstract. In the study by Perez et al, 21 there was no significant difference in peritoneal ultrafiltration and glucose absorption between 50% TPD (14 l) and 7 Â 2 l nontidal APD. Sodium removal with 50% TPD was 181.67 79.8 mmol/treatment vs 138.2774.9 mmol/treatment with 7 Â 2 l non-tidal APD.…”
Section: Sodium Removal and Peritoneal Ultrafiltrationmentioning
confidence: 80%
See 2 more Smart Citations
“…A study of 18 patients receiving 9‐hour automated peritoneal dialysis regimens of five, seven, or nine 2 L exchanges found that the increased inflow/outflow “downtime” of more frequent exchanges generally did not have a negative impact on clearances (11). Mean urea (and creatinine) nightly clearances in the three groups were 7.5, 8.6, and 9.1 L (5.1, 6.1, and 6.4 L) with a similar pattern in both low/low‐average and high/high‐average transporters.…”
mentioning
confidence: 99%